Domestication of new annual pasture legumes for resilient Mediterranean farming systems - Loi A.; Nutt B.J.; Revell C.K. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Sown pastures in Mediterranean environments have historically been based on a limited number of annual legume species, the most successful being subterranean clover (Trifolium subterraneum) and barrel medic (Medicago truncatula). Although these species are widely established, there are many situations where they are not suited, due to biological, edaphic or climatic constraints. Over the past 10 years, a broad range of annual pasture legume species have been evaluated with a particular focus on the needs of emerging farming systems. Species such as biserrula (Biserrula pelecinus), gland clover (Trifolium glanduliferum), eastern star clover (Trifolium dasyurum), bladder clover (Trifolium spumosum), French serradella (Ornithopus sativus) and yellow serradella (Ornithopus compressus) have now been commercialized and are being adopted in mixed farming systems of southern Australia. Frequent resowing is a feature of modern pasture systems and this has directed research effort towards the development of cultivars that have a low cost of seed production. We contend that the development of new pasture legumes needs to consider traits that confer ease of domestication, as well as those delivering high productivity and persistence. Important traits include ease of seed harvest, hard seed and hard seed breakdown patterns, maturity and tolerance to pests and disease. Detailed analysis of some of these traits has revealed new opportunities to reduce the cost of pasture establishment such as under-sowing hard-seed of the pasture legume in a preceding grain crop. The hard-seed will not germinate and compete with the grain crop and the pasture will establish in the following season through natural in situ hard-seed breakdown. Other opportunities are identified for weed management. Pasture improvement in the Mediterranean basin may also benefit from a focus on these plant attributes and allow the development of locally adapted cultivars.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)